1999
DOI: 10.1271/bbb.63.373
|View full text |Cite
|
Sign up to set email alerts
|

Immunopotentiating Activity of Nigerooligosaccharides for the T Helper 1-Like Immune Response in Mice

Abstract: The immunopotentiating activity ef nigereoligosaccharides (NOS), a mixture of nigerose, nigerosyl glucose and nigerosyl maltose, was studied in vitro and in vivo in mice. Mitogen-induced proliferation of splenocytes from normal mice was augmented in a dose-dependent mallner by nigerose of NOS. NOS enhanced interleukin 12 aL-12) and interferon-7 (IFN-7) production by normal splenocytes in the presence of the potent IL-12 inducer, heat-killed Lac-tobaciUusplantaram L-137, in vitro. Consistent with the in vitro f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 25 publications
1
32
1
Order By: Relevance
“…Although these differences were signi®cant only for the NK cell data, the results do strongly suggest that the degree of immune enhancement imparted by B. lactis can be improved by delivering the probiotic in a suitable substrate. Whether these increased immune-enhancing effects re¯ect (indirectly) quantitative increases in number and gut colonizing ability of B. lactis is uncertain; aside from acting as a prebiotic, there is increasing evidence that oligosaccharides can interact directly with probiotic LAB and potentiate their immune-enhancing effects, both in vitro and in vivo (Murosaki et al, 1999). Oligosaccharides derived from milk are thought to have additional health bene®ts besides potentiating probiotic-mediated immune enhancement, including the prevention of pathogen colonization of the gut (Zopf & Roth, 1996;Roberfroid, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Although these differences were signi®cant only for the NK cell data, the results do strongly suggest that the degree of immune enhancement imparted by B. lactis can be improved by delivering the probiotic in a suitable substrate. Whether these increased immune-enhancing effects re¯ect (indirectly) quantitative increases in number and gut colonizing ability of B. lactis is uncertain; aside from acting as a prebiotic, there is increasing evidence that oligosaccharides can interact directly with probiotic LAB and potentiate their immune-enhancing effects, both in vitro and in vivo (Murosaki et al, 1999). Oligosaccharides derived from milk are thought to have additional health bene®ts besides potentiating probiotic-mediated immune enhancement, including the prevention of pathogen colonization of the gut (Zopf & Roth, 1996;Roberfroid, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…3,4) On the other hand, IFN-produced by Th1 cells suppresses IgE production by inhibiting the proliferation of Th2 cells. 5) IL-12, produced mainly by macrophages, stimulates differentiation from naïve T cells to Th1 cells. The balance of activation between Th1 and Th2 cells is considered critical in IgE production.…”
mentioning
confidence: 99%
“…Recently, several studies have suggested that lactic acid bacteria may act as prospective dietary immunoregulators. Some probiotic strains, such as L. casei Shirota and L. plantarum L-137, L. paracasei KW3110 appear to activate macrophages to secrete more pro-inflammatory cytokine IL-12 which can favor Th1 type immunity (6,18,24,33). Furthermore, these probiotic strains have been found to down-regulate antigen-induced serum IgE production in mice (18,21,25).…”
mentioning
confidence: 99%